Influence of the structure of electron-donating aromatic units in organosilicon luminophores based on 2, 1, 3-benzothiadiazole electron-withdrawing core on their absorption-luminescent properties. (August 2018) - Skorotetcky, Maxim S.; Krivtsova, Evgeniya D.; Borshchev, Oleg V.; Surin, Nikolay M.; Svidchenko, Evgeniya A.; Fedorov, Yuriy V.; Pisarev, Sergey A.; Ponomarenko, Sergey A.
Abstract: A series of new linear π-conjugated oligomers consisting of five conjugated rings based on 2, 1, 3-benzothiadiazole (BTD) electron-withdrawing group and various combinations of 2, 5-thiophene and 1, 4-phenylene electron-donating units with terminal trimethylsilyl groups has been synthesized and characterized. Investigation of their absorption-luminescent properties revealed that all of them possess high photoluminescence (PL) quantum yield and large Stokes shift both in diluted solutions and polymer matrix, while in the solid state their PL efficiency decreases. It was found that the main factor influencing the optical properties of the molecules obtained is the type of aromatic fragment directly attached to the central BTD moiety. Changing the chemical structure of the donor aromatic fragments from 1, 1′-biphenyl to 2, 2′-bithiophene allows tuning the PL spectral maximum of the luminophores in wide range from 510 to 660 nm. It was shown that the presence of trimethylsilyl groups in these luminophores is responsible for their increased solubility, enhanced molar extinction coefficients and shortening the excited state lifetime without decreasing the PL efficiency. Graphical abstract: Highlights: Four new organosilicon luminophores based on benzothiadiazole are synthesized. They possess high efficiency and large Stokes shift in solution and polymer matrix. An approach to tune their optical properties in wide spectral range is reported. The nearest donor fragments have the greatest influence on the spectral properties. TMS groups accelerate fluorescence, increase solubility and extinction coefficient.